Fiscal and monetary policies and the cost of sudden stops - Michael M. Hutchison; Ilan Noy; Lidan Wang (University of California, Santa Cruz Institute for International Economics (SCIIE), 2007)
This article investigates the effects of macroeconomic policy (monetary and fiscal) on output growth during financial crises characterized by a sudden stop in net capital inflows in developing and emerging market economies. We investigate 83 sudden stop crises in 77 countries over 1982-2003 using a baseline empirical model to control for the various determinants of output losses during sudden stop crises. Extending the baseline model to account for policies - contractionary as well as expansionary - we measure the marginal effects of policy on output losses. Simple descriptive statistics indicate no apparent correlation between the costs of financial crises and the economic policies pursed at the time. Once controlling for various pre-conditions and other factors, however, we find that monetary and fiscal tightening at the time of a sudden stop crisis significantly worsens output losses.
Keywords: E52; E62; F32; F43; O16; 330; output losses; financial crises; sudden stops; fiscal policy; financial policy; Finanzpolitik; Geldpolitik; Finanzmarktkrise; Kapitalimport; Wirtschaftswachstum; Gesamtwirtschaftliche Produktion; Entwicklungsländer; Schwellenländer